Raphanus Sativus Leaves Ethanol Extract's Effect on Heart Muscle's Nuclear Factor Kappa B (NFkB) in Diabetic Rats - Hendrawati, Asri; Djunet, Nur Aini (Universitas Muhammadiyah Semarang, 2024)
Background: Type 2 diabetes mellitus is characterized by hyperglycemia. Hyperglycemia increases free radicals and oxidative stress that damage heart muscle cells. Nuclear factor kappa B (NFkB) plays an important role in inflammation and cell damage. Radish leaves (Raphanus sativus) are known to have compounds that can control NFkB expression.Objective: To measure the effect of radish leaves on the expression of NFkB in heart muscle.Methods: The study design was experimental laboratory post test control group design. The subjects were diabetic male Wistar rats, weight 150-300 grams, 3-4 months old. Rats were divided into four groups and given treatment orally for 28 days. The 1st group received placebo. The 2nd group received glibenclamide 5 mg/kg BW/day. The 3rd and 4th groups received 50% and 100% ethanol extract of radish leaves. Heart NFkB was measured using immunohistochemistry. Results: Radish leaves ethanol extract 50% and 100% reduced NFkB in the heart muscle better than placebo and glibenclamide 5 mg/kg BW ((p=0.000). There was no difference between radish leaf extract 50% and 100% in reducing heart NFkB expression (p=0.876).Conclusion: Radish leaf extract 50% and 100% reduce NFkB expression better than placebo and glibenclamide 5 mg/kg BW.